KEANEKARAGAMAN FLORA DI AREA PASCA TAMBANG BERAU, KALIMANTAN TIMUR, INDONESIA - Ida Rosita; Sri Wilarso Budi; Imam Gozali; Jenny Rumondang; Saridi (JURNAL AGRIMENT, 2023)
Coal mining activities in Indonesia have a negative impact on the environment. Some vegetations are disturbed even be lost especially in mining with open mine operation. Revegetation is one of activities that can improve the quality of post mining land, which are also included in post mining land reclamation activities. The purpose of this study is to analyze the biodiversity of flora in post-coal mining revegetation area and to compare the condition of vegetation in various revegetation age classes with the condition of vegetation in natural forest. Vegetation data were collected using the plotted line method in natural forest and plot method with the systematic sampling method with random start (revegetation area). The analysis found that overall conditions of revegetation area have more diverse number of species, namely 52 species woody plant species, and 23 herbaceous plant species, compared to the natural forest, which only has 46 woody plant species and 2 herbaceous plant species. Generally, diversity index and species increment in vegetation area at age more than 4 years is higher and approaching the state of natural forest than revegetation area age 0 - 2 years.